MANAGING THE RISK FOR FINTECH LENDING AMID THE GLOBAL PANDEMIC CORONA VIRUS - Usanti, Trisadini Prasastinah; Roro, Fiska Silvia Raden; Setiawati, Nur Utari (UI Scholars Hub, 2021)
The coronavirus (covis-19) is impacting all sectors across the world. Moreover, the covid-19 pandemic will accelerate change in the world economy. That brings both opportunity and danger, says Henry Curr in The Economist. In dealing with global disaster which impacts to the finance and economy world, such as the pandemic of covid-19, fintech lending offers the fastestand the most easy lending service for people in the whole business world nowdays. However, the easy process can cause various problems such as late payment and default in payment. Fintech will suffer from those risks and it can jeopardise the business. Moreover, most of the platforms do not ask for collateral as a requirement. So, in this article, the authors will discuss how fintech should manage their risks in lending using statute and conceptual approach. The results show that fintech should adopt the 5Cs credit analysis (character, capital, capacity, collateral, condition) as a way to minimise their risks. The Financial Services Authority (OJK) has not regulated risk management for fintech. Thus, fintech should follow the existing model from banking institution to manage their risks.